2020
DOI: 10.14198/medcom2020.11.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Neuromarketing y la medición del efecto de la publicidad de influencers en adolescentes

Abstract: Neuromarketing y la medición del efecto de la publicidad de influencers en adolescentes Neuromarketing and effectiveness of influencers' promoted content on teenagers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
4
0
4
Order By: Relevance
“…Are neuromarketing tools capable of measuring these dimensions? A study [39] carried out in June 2019 in a laboratory at the Complutense University of Madrid, with a sample of 19 girls aged between 11 and 16 concluded that consumers perceive influencers' recommendations as more trustworthy, less commercial, and more natural than traditional digital advertising. The results show that the videos that showcase influencers' content are the ones that generate the most attention peaks.…”
Section: Neuromarketing Tools Advertising Effectiveness and Social Mediamentioning
confidence: 99%
“…Are neuromarketing tools capable of measuring these dimensions? A study [39] carried out in June 2019 in a laboratory at the Complutense University of Madrid, with a sample of 19 girls aged between 11 and 16 concluded that consumers perceive influencers' recommendations as more trustworthy, less commercial, and more natural than traditional digital advertising. The results show that the videos that showcase influencers' content are the ones that generate the most attention peaks.…”
Section: Neuromarketing Tools Advertising Effectiveness and Social Mediamentioning
confidence: 99%
“…Mañas-Viniegra, Núnez-Gómez & Tur-Vines (2020) also mention Galvanic Skin Response (GSR) as a neuromarketing technique that records areas of interest according to a subject's eye movements (AOI). Similar to the above, bioelectrical activity is also mentioned, which is known to easily capture through the skin the emotion and attention paid to an advertisement or other stimulus (Ferrer-López, 2020). Gani (2017) states that the internationalisation of services could be a boost for the economic competitiveness of a country; services, especially for emerging countries, are a platform for their economy to grow, and there is recognition of the country brand at the international level .…”
Section: Source: Own Elaborationmentioning
confidence: 99%
“…La Generación Z busca establecer una relación a largo plazo con los streamers de Twitch (García et al, 2022). Los temas generados por influencers causan los mayores picos de atención entre el público joven y el branded content creado por ellos capta aún más su interés (Ferrer, 2020;Rodrigo-Martín, 2021). Ante el grado de influencia de los prescriptores sociales las casas de apuestas se han fijado en ellos como el escaparate ideal para promocionar sus juegos de azar.…”
Section: Hábitos De Consumo En Redes Socialesunclassified